Vasorelaxing Activity of R-(−)-3′-Hydroxy-2,4,5-trimethoxydalbergiquinol from Dalbergia tonkinensis: Involvement of Smooth Muscle CaV1.2 Channels - Cuong, Nguyen Manh; Son, Ninh The; Nhan, Ngu Truong; Khanh, Pham Ngoc; Huong, Tran Thu; Tram, Nguyen Thi Thu; Sgaragli, Giampietro; Ahmed, Amer; Trezza, Alfonso; Spiga, Ottavia; Fusi, Fabio (Planta Medica, 2020)
Dalbergia species heartwood, widely used in traditional medicine to treat various cardiovascular diseases, might represent a rich source of vasoactive agents. In Vietnam, Dalbergia tonkinensis is an endemic tree. Therefore, the aim of the present work was to investigate the vascular activity of R-(−)-3′-hydroxy-2,4,5-trimethoxydalbergiquinol isolated from the heartwood of D. tonkinensis and to provide circular dichroism features of its R absolute configuration. The vascular effects of R-(−)-3′-hydroxy-2,4,5-trimethoxydalbergiquinol were assessed on the in vitro mechanical activity of rat aorta rings, under isometric conditions, and on whole-cell Ba2+ currents through CaV1.2 channels (IBa1.2) recorded in single, rat tail main artery myocytes by means of the patch-clamp technique. R-(−)-3′-Hydroxy-2,4,5-trimethoxydalbergiquinol showed concentration-dependent, vasorelaxant activity on both endothelium-deprived and endothelium intact rings precontracted with the α1 receptor agonist phenylephrine. Neither the NO (nitric oxide) synthase inhibitor Nω-nitro-L-arginine methyl ester nor the cyclooxygenase inhibitor indomethacin affected its spasmolytic activity. R-(−)-3′-Hydroxy-2,4,5-trimethoxydalbergiquinol-induced vasorelaxation was antagonized by (S)-(−)-Bay K 8644 and unaffected by tetraethylammonium plus glibenclamide. In patch-clamp experiments, R-(−)-3′-hydroxy-2,4,5-trimethoxydalbergiquinol inhibited IBa1.2 in a concentration-dependent manner and significantly decreased the time constant of current inactivation. R-(−)-3′-Hydroxy-2,4,5-trimethoxydalbergiquinol likely stabilized the channel in its closed state, as suggested by molecular modelling and docking simulation to the CaV1.2 channel α1c subunit. In conclusion, D. tonkinensis species may represent a source of agents potentially useful for the development of novel antihypertensive drugs.
Keywords: Dalbergia tonkinensis; Fabaceae; R-(−)-3′-hydroxy-2,4,5-trimethoxydalbergiquinol; rat aorta rings; docking simulation; CaV1.2 channel; open-chain neoflavonoid; patch clamp